Model Penelitian dan Pengembangan Materi Ajar BIPA (Bahasa Indonesia bagi Penutur Asing) - Defina Defina (Indonesian Language Education and Literature)
The objectives of this research are (1) to analyze the development model of Indonesian language teaching materials for foreign speakers and (2) combine the existing models. The analysis of this theory based on the results of research and development has been undertaken by BIPA IPB. The research had been conducted from August 2015 to Februrai 2017. Eight models were the research objects to analyze, namely a) ADDIE models, b) Dick, Carey, and Carey models, c) Borg and Gall models, d) ASSURE models, Kemp models, f) Tomlinson models, g) Brown models, and h) Jolly and Bolitho models.The research result shows models that have been modified in three main parts, namely 1) preparation, 2) planning, and 3) development-evaluation. These three parts can be broken down into 17 sections, such as 1) curriculum, 2) needs analysis, 3) syllabus, 4) text collection, 5) text selection, 6) material creation, 7) draft I, 8) preparation of test questions, 9) one to one test, 10) revision I , 11) draft II, 12) small group trial, 13) revision II, 14) draft III, 15) effectiveness test, 16) revision III, and 17) final product. The conclusion is that each model has its advantages and disadvantages. The development of Indonesian language teaching material models for foreign speakers can be undertaken by combining development research models that have been formulated by experts. Tujuan penelitian ini adalah untuk menganalisis model pengembangan materi ajar bahasa Indonesia bagi penutur asing dan mengombinasikan model-model yang ada. Analisis teori ini berdasarkan hasil  penelitian dan pengembangan yang telah dilakukan di BIPA IPB. Penelitian dilakukan sejak Agustus 2015--Februari 2017.  Objek yang dianalisis ada delapan model: a)  model ADDIE, b) model Dick, Carey, dan Carey, c) model Borg dan Gall, d) model ASSURE, e) model Kemp, f) Tomlinson, g) Brown, dan h) Jolly dan Bolitho. Hasilnya, dari delapan model yang dianalisis, dapat dirumuskan model yang telah dimodifikasi. Ada tiga bagian utamanya, yaitu 1) persiapan, 2) perencanaan, dan 3) pengembangan-evaluasi. Dari 3 bagian itu dapat diuraikan menjadi 17 bagian: 1) kurikulum, 2) analisis kebutuhan, 3) silabus, 4) pengumpulan teks, 5) pemilahan teks, 6) pengkreasian materi, 7) draf I, 8) penyusunan soal tes, 9) uji one to one, 10) revisi I, 11) draf II, 12) uji coba kelompok kecil, 13) revisi II, 14) draf III, 15) uji efektivitas, 16) revisi III, dan 17) produk final. Simpulannya adalah setiap model itu memiliki kelebih dan kekurangan. Pengembangan model materi ajar bahasa Indonesia bagi penutur asing dapat dilakukan dengan mengombinasikan model-model penelitian pengembangan yang sudah dirumuskan para pakar.